A study on the Development and Effect of Survival swimming standard Curriculum - Boum, Kim; Jin-hyoung, Jeong; Jun-tae, Kim; Sang-sik, Lee (International Journal of Advanced Science and Technology, 2019)
Survival swimming standard curriculum was developed and its efficacy was examined 23 3rd grade elementary school student participated in the survival swimming standard curriculum, and 48 3rd grade elementary school student participated in the leaf float(n=24) and general swimming(n=24) curriculum. Their scores on various variables were compared with those of the non-treatment control group. For the self-compassion enhancement program group, basic psychological needs and performance assessment significantly increased, respectively. These findings indicated that the survival swimming standard curriculum exhibited relative benefits of its effects compared to the other curriculum. Lastly, contributions of this study to an integrative understanding of the process of survival swimming are discussed. Limitations and suggestions for future research are also discussed.